Effects of consecutive long-haul travel on jet-lag symptoms: case study of a national water polo team preparing for world-class events - Botonis, P. G.; Toubekis, A. G.; Hill, D. W. (International Journal of Sports Physiology and Performance, 2026)
Purpose: To describe jet-lag symptoms in the days following 3 long-haul transmeridian travel.